2023
DOI: 10.1007/s10103-023-03727-z
|View full text |Cite
|
Sign up to set email alerts
|

Laser acupuncture improving functional chronic constipation in children: a randomized controlled trial

Abstract: Functional chronic constipation (FCC) is a disorder caused by low fiber consumption, lack of fluid intake, lack of mobility, or side effects of medications. The objective of this study was to compare the effects of laser acupuncture and the commonly used osmotic laxative, lactulose (as the control), both combined with behavioral therapy and dietary modification, on children with FCC in a randomized controlled trial (RCT). Forty children were randomly chosen, aged 5–15 years with FCC, and randomized into two eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Also, our results were in agreement with a study in 2010; their findings were consistent with the observed changes in biochemical markers related to skeletal muscle recovery and the decrease in muscle fatigue [ 21 , 22 ]. Another study conducted in 2016 found that the low-level laser may help in increasing the recruitment of muscle fibers, additionally increasing the onset time of the spastic muscle fatigue, and decreasing pain intensity in stroke patients with spasticity, as has been observed in healthy subjects and athletes [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Also, our results were in agreement with a study in 2010; their findings were consistent with the observed changes in biochemical markers related to skeletal muscle recovery and the decrease in muscle fatigue [ 21 , 22 ]. Another study conducted in 2016 found that the low-level laser may help in increasing the recruitment of muscle fibers, additionally increasing the onset time of the spastic muscle fatigue, and decreasing pain intensity in stroke patients with spasticity, as has been observed in healthy subjects and athletes [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Laser acupuncture involves irradiating acupoint skin with a low-intensity laser beam, producing various effects that penetrate deep into body tissues to treat diseases with anti-inflammatory and analgesic functions [ 114 , 115 ]. As a non-invasive, painless, safe, and effective method [ 116 , 117 ], laser acupuncture has been primarily used to treat neurological diseases [ 118 ], knee osteoarthritis [ 119 ], and functional constipation [ 120 ], but its application in treating PD remains limited. The scope of treatment with laser acupuncture and Mo still requires comprehensive and multi-level research.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, techniques like fire acupuncture, superficial acupuncture, and laser acupuncture are distinct from what people know as standard acupuncture. [3][4][5] Moreover, in Chinese, the term "acupuncture" can be defined as needling plus moxibustion. [6] Given the existence of various acupuncture related interventions, it becomes important for researchers to precisely define the intervention concept.…”
Section: Standardize the Concepts Of Acupuncturementioning
confidence: 99%